2019
DOI: 10.1111/sji.12743
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic effects of recombinant adenovirus encoding interleukin 12 in experimental pulmonary tuberculosis

Abstract: High dose of Mycobacterium tuberculosis (Mtb) strain H37Rv administered by intratracheal injection in BALB/c mice induce progressive tuberculosis (TB). In this model, during the first month there is a temporal control of bacillary growth, in coexistence with macrophage activation, granuloma formation and Th-1 response. Then, bacterial proliferation recommences, accompanied by progressive pneumonia and decreasing expression of protective cytokines (IFN-γ and TNF-α).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Modulating T‐cell responses to restore immunity can be mediated by vaccination or T‐cell cytokine therapies. Administration of IL‐12 141 or IL‐24 142 or blocking Th2 cytokine IL‐4, 131 promotes Th1 responses with lasting IFN‐γ production that may be preferred over IFN‐γ administration. Which of these strategies is (most) efficacious and which patients benefit most from this therapy remains to be addressed.…”
Section: Personalized and Combinatorial Hdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulating T‐cell responses to restore immunity can be mediated by vaccination or T‐cell cytokine therapies. Administration of IL‐12 141 or IL‐24 142 or blocking Th2 cytokine IL‐4, 131 promotes Th1 responses with lasting IFN‐γ production that may be preferred over IFN‐γ administration. Which of these strategies is (most) efficacious and which patients benefit most from this therapy remains to be addressed.…”
Section: Personalized and Combinatorial Hdtmentioning
confidence: 99%
“…Administration of IFNγ also reduced Mav growth in murine macrophages,137 and improved clinical outcome (ie, decreased respiratory symptoms and mortality) in several but not all Mav-infected individuals,[138][139][140] suggesting potential of IFNγ as HDT in both Mtb and Mav infections. In vivo administration of IL-12, a key cytokine that drives Th1 skewing, enhanced IFNγ and TNFα responses and significantly reduced bacterial burden in an acute mouse TB model 141. Similarly, restoring IL-24 expression in a mouse TB model enhanced Th1-responses and IFNγ production, with concomitant improved survival and reduced bacterial loads 142.…”
mentioning
confidence: 99%
“…The M1 phase induces the expression of several genes through IFN-γ such as IL-1β, IL-12, TNF-α, and iNOS/NOS2 (inducible NO synthase), the products of which result in bacterial clearance. For instance, TNF-α signaling results in apoptosis; IL-1β signaling results in ROS generation, IL-12 is a determiner of protective immunity against Mtb (Mata-Espinosa et al, 2019 ) which is produced by macrophages upon interaction with Mtb antigens. The secreted IL-12 signals through the JAK-STAT pathway to induce IFN-γ that in turn switches on various antimicrobial defenses.…”
Section: Mycobacterium Tuberculosis Infection Reallocates MImentioning
confidence: 99%
“…Similarly, Mata-Espinosa et al. demonstrated that intranasal administration of a genetically engineered adenoviral vector expressing mouse IL-12 during Mtb infection resulted in a significant reduction in pulmonary bacterial loads ( Mata-Espinosa et al., 2019 ). However, the effects of IL-12 supplementation during antibiotic treatment of Mtb-infected mice to the best of our knowledge have never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Elıás-Loṕez et al found that oral administration of extracts of transgenic tomatoes expressing recombinant murine IL-12 resulted in increased levels of the cytokine in the circulation and bronchoalveolar space of Mtb-infected mice, consequently improving the control of bacterial replication by the animals (Elias-Lopez et al, 2008). Similarly, Mata-Espinosa et al demonstrated that intranasal administration of a genetically engineered adenoviral vector expressing mouse IL-12 during Mtb infection resulted in a significant reduction in pulmonary bacterial loads (Mata-Espinosa et al, 2019). However, the effects of IL-12 supplementation during antibiotic treatment of Mtbinfected mice to the best of our knowledge have never been investigated.…”
Section: Strategies Aimed At Boosting Th1mentioning
confidence: 99%